2021
DOI: 10.1080/23311975.2021.1924923
|View full text |Cite
|
Sign up to set email alerts
|

Influence of servicescape on behavioural intentions through mediation and moderation effects: A study on Malaysia’s full-service restaurants

Abstract: servicescape on consumption evaluation and consumer behaviour. This is the first study on full-service restaurant context, investigating servicescape as a higherorder construct. Full-service restaurants need to be conscious of servicescape elements to maintain an acceptable level of crowding and to positively influence consumer behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…The concept is often used in the field of the service industry and in psychology (Sohaib and Kang, 2015; Cheng et al , 2020; Zimmerman, 2012; Rajaguru, 2014; Teh et al , 2014). In the field of the service industry, many researchers have conducted studies about the positive influences of restaurant servicescape on customers’ perceptions, such as eWOM and repurchase intentions (Asghar Ali et al , 2021); pleasure and satisfaction level (Lin and Mattila, 2010); as well as the interactions between customers and employees (Kaminakis et al , 2019). The servicescape model has been widely used in the tourism and hospitality industry.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The concept is often used in the field of the service industry and in psychology (Sohaib and Kang, 2015; Cheng et al , 2020; Zimmerman, 2012; Rajaguru, 2014; Teh et al , 2014). In the field of the service industry, many researchers have conducted studies about the positive influences of restaurant servicescape on customers’ perceptions, such as eWOM and repurchase intentions (Asghar Ali et al , 2021); pleasure and satisfaction level (Lin and Mattila, 2010); as well as the interactions between customers and employees (Kaminakis et al , 2019). The servicescape model has been widely used in the tourism and hospitality industry.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Numerous scholars [28-31] have projected social servicescape to be a separate dimension of servicescape and have suggested social servicescape should be examined separately. For example, in a study conducted in Malaysia on restaurant servicescape by Asghar et al [47], they found that both physical and social servicescape equally affected consumer satisfaction. Asghar et al [47] reported positive relationship of restaurant's social servicescape with satisfaction in their study.…”
Section: Social Servicescape and Satisfactionmentioning
confidence: 99%
“…For example, in a study conducted in Malaysia on restaurant servicescape by Asghar et al [47], they found that both physical and social servicescape equally affected consumer satisfaction. Asghar et al [47] reported positive relationship of restaurant's social servicescape with satisfaction in their study. Chang [48] in a study conducted on hot spring resorts of Taiwan found social servicescape predicted satisfaction strongly than physical servicescape.…”
Section: Social Servicescape and Satisfactionmentioning
confidence: 99%
“…Crowdedness in a restaurant can be a sign of popularity, reasonable pricing, or good food quality, which is why crowdedness has been reported as a pivotal antecedent of purchase intentions ( Thoo et al, 2018 ; Grewal and Stephen, 2019 ; Milman et al, 2020 ). Crowding is a common occurrence in the context of a restaurant, which consumers encounter at different stages of their decision-making process ( Asghar Ali et al, 2021 ). Because of inconclusive research on crowding in the specific context of a restaurant, it will be interesting to investigate the moderating effect of perceived crowding on the relationship between online reviews and purchase intentions.…”
Section: Literature Reviewmentioning
confidence: 99%